Flood Vulnerability Analysis Using Remote Sensing and GIS: A Case Study of Sidoarjo Regency - Hery Setiawan Purnawali; Teguh Hariyanto; Danar Guruh Pratomo; Nurin Hidayati (Institut Teknologi Sepuluh Nopember, 2017)
Sidoarjo Regency is one of the regencieslocatedin East Java Province Indonesia.Topography of some area in Sidoarjocan be categorized asin low altitude topography, so it makes this regency haspotential risk for flood disaster. Flood incident in Sidoarjo occurs almost every year. The cause of flooding in this district is an accumulation of several factors, such as heavy rainfall in the rainy season for every year, the low altitude areas in several sub-districts, land cover dominated roads and buildings in the some sub-districts, and the existence of several rivers flowing through the district. Application of Geographic Information System (GIS) and remote sensing is generated in this study to present information on the mapping of flood vulnerability zones in Sidoarjo. Integration of satellite and GIS datasets are carried out to prepare the flood zonation mapping of Sidoarjo Regency. Rainfall data fromTropical Rainfall Measuring Mission (TRMM), topographic map, land coverand the distance to main channel data are the datasetsused to identify the flood vulnerability. Flood vulnerability information includes the spatial distribution of flood hazard vulnerability in all sub-districs of Sidoarjo Regency. Spatial information is represented in the form of a map image. By knowing the spatial distribution, it can be known the level of vulnerability of areas to flooding. Most of Sidoarjo regency is flood vulnerable area, which is 76.24% or 658,702,719.91 sqm. It consist of 33.14% very high vulnerable area and 43.10% high vulnerable area. Very high vulnerable flood-prone areas in Sidoarjo Regency include most area of Jabon, Porong, Tanggulangin, Balongbendo, Krembung, Taman, and Waru sub-districts, while others are some parts of Candi, Sidoarjo, Buduran, and Gedangan sub-districts. High vulnerable flood-prone area include Tarik, Prambon, Tulangan, Wonoayu, and Sukodono sub-districts. The most dominant factors causing flooding in Sidoarjo Regency is the change of land cover, heavy rainfall, and high drainage density, while other factor also contributing to future flood vulnerability are land subsidence.